Tranexamic acid for reducing mortality in emergency and urgent surgery (2012)
ABSTRACT: BackgroundEmergency or urgent surgery, which can be defined as surgery which must be done promptly to save life, limb or functional capacity,is associated with a high risk of bleeding and death. Antifibrinolytic agents, such as tranexamic acid, inhibit blood clot breakdown(fibrinolysis) and can reduce perioperative bleeding. Tranexamic acid has been shown to reduce the need for a blood transfusion in adultpatients undergoing elective surgery but its eHects in patients undergoing emergency or urgent surgery are unclear.ObjectivesTo assess the eHects of tranexamic acid on mortality, blood transfusion and thromboembolic events in adults undergoing emergency orurgent surgery.Search methodsWe searched the following electronic databases: the Cochrane Injuries Group Specialised Register (22 August 2012); Cochrane CentralRegister of Controlled Trials (2012, Issue 8 of 12); MEDLINE (OvidSP) (1950 to week 2 August 2012); PubMed (1 June 2012 to 22 August2012); EMBASE (OvidSP) (1980 to Week 33 2012); ISI Web of Science: Conference Proceedings Citation Index-Science (CPCI-S) (1990 to 22August 2012); ISI Web of Science: Science Citation Index Expanded (SCI-EXPANDED) (1970 to 22 August 2012). We also searched online trialsregisters on 22 August 2012 to identify unpublished studies.Selection criteriaRandomised controlled trials comparing tranexamic acid with no tranexamic acid or placebo in adults undergoing emergency or urgentsurgery.Data collection and analysisTwo authors examined titles, abstracts and keywords of citations from the electronic databases for eligibility and extracted data for analysisand risk of bias assessment. Outcome measures of interest were mortality, receipt of a blood transfusion, units of blood transfused,reoperation, seizures and thromboembolic events (myocardial infarction, stroke, deep vein thrombosis and pulmonary embolism).Main resultsWe identified five trials involving 372 people that met the inclusion criteria. Three trials (260 patients) contributed data to the analyses.The eHect of tranexamic acid on mortality (RR 1.01; 95% CI 0.14 to 7.3) was uncertain. However, tranexamic acid reduced the probabilityof receiving a blood transfusion by 30% although the estimate was imprecise (RR 0.70; 95% CI 0.52 to 0.94). The eHects on deep venousthrombosis (RR 2.29; 95% CI 0.68 to 7.66) and stroke (RR 2.79; 95% CI 0.12 to 67.10) were uncertain. There were no events of pulmonaryembolism or myocardial infarction. None of the trials reported units of blood transfused, reoperation or seizure outcomes.